Mineralisation and Oxygen Isotope Zonation of Chatree Epithermal Gold-Silver Deposit, Phetchabun Province, Central Thailand - K Zaw; S Meffre; S Golding; J McPhie; S Suphananthi; R James (The Australasian Institute of Mining and Metallurgy, 2008)
The Chatree deposit is located in the central portion of Loei Fold Belt, which extends from Lao PDR in the north through centralThailand to Cambodia in the south. Epithermal gold-silver mineralisation at Chatree occurs as veins/veinlets and stockworks with minor breccia in volcaniclastic and volcano-sedimentary rocks of andesitic to basaltic andesite composition and Permo-Triassic age. This preliminary oxygen isotope study mainly focuses on vein quartz of Au-Ag bearing mineralization (Stage 2) and a few samples of late Stage 4 quartz ¦ calcite veins. Quartz from Au-Ag bearing mineralisation has oxygen isotope values ranging from 8.1 to 12.3ë with the lowest values generally occurring at the deeper level (140 m below the surface). The late barren quartz ¦ calcite veins (Stage 4) tend to have higher oxygen isotope values ranging from 11.9 to 12.0ë. The oxygen isotope composition of the Chatree ore fluids were calculated at 250¦C, 300¦C and 350¦C based on homogenisation temperatures of fluid inclusions. The calculated oxygen isotopic composition of the Chatree ore fluid ranges between -1 and 6ë that overlaps with both meteoric and magmatic compositions. This shift in oxygen isotope compositions may relate to processes such as water rock-interaction and/or mixing of meteoric and magmatic fluids. It is interesting to note that the lowest quartz oxygen isotope values are spatially more or less confined to the prominent structures in the centre of the major ore zones. These structures may have been acted as conduits for higher temperature magmatic fluids. The quartz oxygen isotope values increase outwards from the centre of the main ore zones to the margin of the pits possibly due to mixing of magmatic fluids with lower temperature meteoric water. Whole rock oxygen and hydrogen isotope studies are in progress to investigate isotopic trends in the wall rock away from the ore zone. The systematic variation of oxygen isotopes in quartz from the mineralised veins and adjacent wall rocks could potentially be used as a vector to ore. An EXTENDED ABSTRACT is available for download. A full-length paper was not prepared for this presentation.